Evaluation of the sociodemographic, clinical and criminal characteristics of the individuals with probation due to substance use - Sehlikoglu, Kerem; Özkan, Ömer Lütfi; SEHLIKOGLU, Seyma; Eğilmez, Oğuzhan Bekir; Kafadar, Huseyin (The Bulletin of Legal Medicine, 2022)
Objective: The prevalence of substance use and related disorders has been ever-increasing in Turkey and the world. Probation system has been implemented in Turkey since 2006 year. The aims of study are to examine the relationships between sociodemographic, clinical features, criminal records of individuals who have probation and treatment and to evaluate the results of the application. Methods: Of 145 individuals who applied to the probation office were prospectively included in terms of their sociodemographic, substance use, forensic medical features, and the psychiatric diagnosis. During the implementation of the probation system, substance level analysis of urine samples was carried out as three and six-visit programs. Results: Of 142 (97.9%) participants were male and 3 (2.1%) were female. In the study, it was observed that individuals were mostly male, single, aged between 18-30 years, had a low level of education and income, and used marijuana as a substance. Multiple substance use histories were determined in 59.3% of the cases. Conclusion: It was concluded that individuals should be educated about the substance since primary school period and social awareness should be provided. In addition, individuals with a low educational level were more likely to commit crimes and attended the six-visit program. It was thought that implemented both programs were similarly efficient and these programs should be continued effectively. Finally, it was evaluated that better clinical results could be obtained if a detailed psychiatric examination was performed in individuals with multiple substance use.